Rethinking cross-border talent management: The emerging markets perspective - Gandhok, Tejpavan (Institutional Knowledge at Singapore Management University, 2014)
A closer look at the relatively little understood issue of how and why emerging market MNCs manage their senior talent for international growth leads us to question the conventional wisdom on talent management practices.